Assessment of noise pollution in northeastern Peru - Ruiz-Tafur, Irael (2025)
The district of Bagua Grande, province of Utcubamba, Amazonas region, faces a severe noise pollution problem due to its rapid population growth and the consequent increase in vehicular traffic. Factors such as excessive use of horns, the age of the vehicle fleet, and the lack of mufflers intensify the noise, impacting quality of life. The main objective of this research was to evaluate noise pollution in the district and compare sound pressure levels (SPL) with Supreme Decree No. 085-2003-PCM. The methodology used followed the National Protocol for Environmental Noise Monitoring (Supreme Decree No. 227-2013-MINAM). Monitoring was carried out between October and December 2020, during daytime hours (6:00 a.m. to 8:00 a.m. and 12:00 p.m. to 2:00 p.m.). Sixty points (40 urban and 20 commercial) were measured at a height of 1.5 m, totaling 180 measurements. The results concluded that there was widespread non-compliance with the National Environmental Quality Standard (ECA) of 60 dB. In the urban area, the La Esperanza sector was the most affected, with 9 out of 10 points exceeding the permitted limit, followed by San Martín (7 out of 10 points). The most critical situation was recorded in commercial areas, particularly the Mercado Modelo market, where 100% of the points sampled exceeded 70 dB, with peaks of up to 95.4 dB at the Parada Municipal market. It is concluded that Bagua Grande has noise levels that pose a significant risk to public health and require urgent regulatory and enforcement action.